Money velocity in an endogenous growth business cycle with credit shocks - Szilárd Benk; Max Gillman; Michal Kejak (Magyar Nemzeti Bank, 2007)
The paper sets the neoclassical monetary business cycle model within endogenous growth, adds exchange credit shocks, and finds that money and credit shocks explain much of the velocity variation. The role of the shocks varies across sub-periods in an intuitive fashion. Endogenous growth is key to the construction of the money and credit shocks since these have similar effects on velocity, but opposite effects upon growth. The model matches the data's average velocity and simulates well velocity volatility. Its Cagan-like money demand means that money and credit shocks cause greater velocity variation the higher is the nominal interest rate.
Keywords: E13; E32; E44; 330; velocity; business cycle; credit shocks; endogenous growth; Geldumlaufgeschwindigkeit; Neue Wachstumstheorie; Konjunktur; Schock; Theorie